Structured Evaluation in Mentoring Programs for Student Career Development in Higher Education - Chada, Narin Suchada (Metromedia, 2023)
Mentoring programs in higher education have an important role in students' career development and their readiness for work. However, one of the problems that often occurs is the lack of structured evaluation of the program, which can have a significant impact on the effectiveness and achievement of students' career development goals. Without clear and systematic evaluation, universities cannot identify problems that arise during the program, such as mismatches between mentor and mentee expectations, or obstacles in communication and time. In addition, limited evaluation also hinders continuous improvement and optimization of mentoring programs, which in turn can affect the quality of mentoring relationships and the job readiness of students. This study aims to analyze the impact of the lack of structured evaluation on mentoring programs in higher education and provide recommendations on the importance of implementing continuous evaluation to ensure that the career development goals of students are achieved. Based on the results of the analysis, it is recommended that universities design a comprehensive evaluation system, involve mentors and mentees in the assessment, and ensure that improvements are made based on the evaluation results to improve the quality of the program. Thus, mentoring programs are expected to be more effective in supporting students' career development and preparing them for success in the world of work.